2019
DOI: 10.18632/oncotarget.26674
|View full text |Cite
|
Sign up to set email alerts
|

The value of arterial spin labelling in adults glioma grading: systematic review and meta-analysis

Abstract: This study aimed to evaluate the diagnostic performance of arterial spin labelling (ASL) in grading of adult gliomas. Eighteen studies matched the inclusion criteria and were included after systematic searches through EMBASE and MEDLINE databases. The quality of the included studies was assessed utilizing Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2). The quantitative values were extracted and a meta-analysis was subsequently based on a random-effect model with forest plot and joint sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 55 publications
0
26
1
Order By: Relevance
“…Studies using small-size ROI and VOI demonstrated higher sensitivity and speci city in distinguishing LGG and HGG. According to meta-analysis performed by Alsaedi et al (2019) maxTBF was proved to be more informative rather than meanTBF in differentiating cerebral glioma grades.…”
Section: Discussionmentioning
confidence: 97%
“…Studies using small-size ROI and VOI demonstrated higher sensitivity and speci city in distinguishing LGG and HGG. According to meta-analysis performed by Alsaedi et al (2019) maxTBF was proved to be more informative rather than meanTBF in differentiating cerebral glioma grades.…”
Section: Discussionmentioning
confidence: 97%
“…All studies with small-size ROI and VOI demonstrated higher sensitivity and specificity in distinguishing of low- and high-grade gliomas. According to a meta-analysis performed by Alsaedi et al 33 , maxTBF has been proven to be more informative than mean TBF in differentiating between cerebral glioma grades. We have acquired the same results in our study as well.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial neovascularization is an important histopathologic feature that reflects glioma malignancy [27] and increased vascularity is typically associated with a higher tumor grade and aggressiveness [5,7,[28][29][30]. PWI techniques, such as DSC-MRI and ASL-MRI, have been widely used for the assessment of tumoral vascularity in vivo [31] and help to preoperatively predict grading of gliomas [1,7,25,[32][33][34][35][36][37]. Maia et al [30] found that quantitative perfusion measurements predicted tumor biologic activity and survival better than histopathologic grade did.…”
Section: Discussion/conclusionmentioning
confidence: 99%